Lifetime history of hypertensive disorders of pregnancy is associated with shorter sleep duration and more sleep disturbance in midlife: results from the Project Viva women’s health cohort - Kimia Heydari; Sheryl L. Rifas-Shiman; Suzanne M. Bertisch; Elizabeth B. Klerman; Jorge E. Chavarro; Emily Oken; Karen M. Switkowski (Biology of Sex Differences)
Abstract Background Hypertensive disorders of pregnancy (HDP) are associated with worse prenatal and perinatal sleep health and higher cardiovascular disease risk beyond the peripartum period. The relationship of HDP with sleep health in midlife, when sleep problems are common, remains unclear. Methods We studied women enrolled in Project Viva during early pregnancy (1999–2002) with sleep outcomes assessed in midlife (2017–2024). We determined lifetime HDP via medical records from the index pregnancy and self-report both at enrollment and during midlife. Outcomes were (i) self-reported sleep duration and sleep quality, using the patient-reported outcomes measurement information system sleep disturbance and sleep-related impairment instruments at mean 52.3yrs; and (ii) objectively measured 5-day sleep duration and efficiency by wrist actigraphy at mean 55.8yrs in a subset. We performed linear and logistic regression models adjusted for enrollment age, education, parity, household income, pre-pregnancy BMI, race, and ethnicity and considered modification by social determinants of health. Results Of 767 participants, 23% had a lifetime history of HDP, 4% had ≥ 2 episodes, and 7% had HDP during their last pregnancy. Mean (SD) daily sleep duration was 7.1 (1.0) hours by self-report and 6.7 (1.0) hours by actigraphy. Any (vs. no) lifetime HDP was associated with shorter self-reported (-8 min, 95% CI: -19, 2) and actigraphy-measured (-16 min, 95% CI: -31, -1) sleep duration. Estimates were stronger but with wider CIs for those with ≥ 2 (vs. no) HDP episodes (e.g., -23 min, 95% CI: -53, 6 for actigraphy-measured sleep duration). Mean (SD) sleep disturbance T-score was 48.6 (7.4) and sleep-related impairment was 45.8 (8.5). Any lifetime HDP (vs. none) was associated with higher (worse) sleep disturbance T-score (1.85 points, 95% CI: 0.28, 3.42) with stronger associations for ≥ 2 HDP episodes (3.41 points, 95% CI: 0.17, 6.65) and for HDP in the last pregnancy (3.63 points, 95% CI: 0.70, 6.57). HDP was not associated with self-reported sleep-related impairment or sleep efficiency. Conclusions History of HDP was associated with shorter sleep duration and higher sleep disturbance in midlife. Future work should investigate the contribution of sleep health to associations of HDP exposure with cardiovascular disease risk in later life.